Cue-induced cocaine craving enhances psychosocial stress and vice versa in chronic cocaine users - Kexel, Ann-Kathrin; Kluwe-Schiavon, Bruno; Baumgartner, Markus R.; Engeli, Etna J. E.; Visentini, Monika; Kirschbaum, Clemens; Seifritz, Erich; Ditzen, Beate; Soravia, Leila M.; Quednow, Boris B. (Translational Psychiatry, 2022)
Stress and craving, it has been found, contribute to the development and maintenance of and relapse in cocaine use disorder. Chronic cocaine users (CU), previous research has shown, display altered physiological responses to psychosocial stress and increased vegetative responding to substance-related cues. However, how psychosocial stress and cue-induced craving interact in relation to the CU’s physiological responses remains largely unknown. We thus investigated the interaction between acute psychosocial stress and cocaine-cue-related reactivity in 47 CU and 38 controls.